Supply Chain Management UMKM Tape Singkong Di Kota Tape Bondowoso - Ningrum, Nurita; Alfiatunningsih, Ira (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
Supply chain management (supply chain management) was originally the science of logistics management as an integrated system that coordinates all processes within the organization/company that prepare and deliver products/goods to consumers. This process includes planning (plan), input sources (source), namely raw materials from suppliers, transformation, distribution, warehousing (deliver), information systems, payment for goods, until the goods are consumed by consumers, and the final stage is product/goods return services ( returns). The return process includes recycling activities, returning damaged goods, or replacing damaged goods with new goods. This research was conducted at UMKM tape handayani 82 in Bondowoso district. The formulation of the problem is as follows: 1) What are the stages of the tape handayani 82 supply chain in Bondowoso district? 2) What is the condition of the tape handayani 82 supply chain in Bondowoso district? While the research objectives in this thesis are: 1) To determine the stages of the tape handayani 82 supply chain in Bondowoso Regency. 2) To find out the condition of the tape handayani 82 supply chain in Bondowoso Regency. The approach used is to use a qualitative approach, a descriptive research type. As for the determination of informants using purposive sampling technique. Methods of data collection using observation, interviews, documentation. From the research results it can be seen that the application of supply chain management, based on data analysis concluded that the process in the tape handayani 82 industry uses the stages in the supply chain. Supporting and inhibiting factors for supply chain management on tape 82, namely: supporting factors, namely communication to customers via WhatsApp media, while inhibiting factors, namely the impact of Covid 19 so that there are many ingredients that are lacking and good quality cassava is only a few and expensive